2017
DOI: 10.1021/jacs.7b01039
|View full text |Cite
|
Sign up to set email alerts
|

Structural Reorganization of Pt(111) Electrodes by Electrochemical Oxidation and Reduction

Abstract: The surface restructuring of Pt(111) electrodes upon electrochemical oxidation/reduction in 0.1 M HClO4 was studied by in situ grazing-incidence small-angle X-ray scattering and complementary scanning tunneling microscopy measurements. These methods allow quantitative determination of the formation and structural evolution of nanoscale Pt islands during potential cycles into the oxidation region. A characteristic ripening behavior is observed, where these islands become more prominent and homogeneous in size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 65 publications
10
121
0
Order By: Relevance
“…In addition, both the in‐plane compressive strain and the coherence lengths decrease while the out‐of‐plane components increase. Our observations are interpreted as effects of Pt oxidation and reduction, which may result in roughening, strain relaxation and thickening of the Pt overlayer …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, both the in‐plane compressive strain and the coherence lengths decrease while the out‐of‐plane components increase. Our observations are interpreted as effects of Pt oxidation and reduction, which may result in roughening, strain relaxation and thickening of the Pt overlayer …”
Section: Resultsmentioning
confidence: 99%
“…Elucidating the active surface phase in situ and understanding its degradation mechanisms is essential to optimise the electrocatalytic efficiency and durability at the cathode of low‐temperature fuel cells . In situ synchrotron studies such as GI‐XRD on model electrode surfaces are key to understand the structure–activity‐stability relationships in electrocatalysis . Here, we aim to shed light on the formation of the Pt overlayer on Gd/Pt(111) single‐crystalline electrodes and correlate the overlayer strain with the electrochemical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of random, non‐well‐defined defects on Pt surfaces can be achieved upon cycling the electrode to high potentials . It has been widely reported that by this electrochemically procedure the generation of defects can be followed by the highly regular evolution of the voltammogram, and, after a given number of cycles, depending of the upper potential limit employed, the current‐potential profile reaches a limiting shape indicating that a steady‐state distribution and coverage of random defects have been reached …”
Section: Introductionmentioning
confidence: 99%
“…The electrochemistry of Pt materials is critical in both electrooxidation of fuels and electroreduction of dioxygen. [7][8][9] It is very important to understand the surface chemistry of Pt for fuel cells. [3,6] For the cathodic reaction of oxygen reduction reaction, Pt materials could be undermined by the irreversible surface change and Pt dissolution with intensive cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Much qualitative information of surface species can be extracted from CV combined with in situ surface technics such as Fourier Transformation Infrared Spectroscopy (FTIR), [10,11] Raman spectroscopy, [12] scanning tunneling microscopy (STM), [7,9] and surface X-ray scattering. Much qualitative information of surface species can be extracted from CV combined with in situ surface technics such as Fourier Transformation Infrared Spectroscopy (FTIR), [10,11] Raman spectroscopy, [12] scanning tunneling microscopy (STM), [7,9] and surface X-ray scattering.…”
Section: Introductionmentioning
confidence: 99%